Enhancing Resource Access through Cooperative Membership: The Case of the Teachers of the Luakan National High School, Philippines - De Leon, Patrick (Journal of Management Studies and Development, 2025)
This study investigated the effect of cooperative membership on the resource access of the teachers of the Luakan National High School in Dinalupihan, Bataan, Philippines. The study aimed to: determine whether there is a significant difference in the estimated monthly consumption expenditures of the teachers before and after joining their consumer cooperative; explain how cooperative membership enhances the teachers’ resource access and turns their capabilities into functionings; and discuss the problems being faced by the cooperative members. The needed data for the study were obtained through an online survey of 34 members of the cooperative and a face-to-face interview of 12 of their officials. The study found a significant difference between the estimated monthly consumption expenditures of the teachers before (M = 7,514.71, SD = 5,240.41) and after (M = 9,638.24, SD = 5,886.66) joining their cooperative; t = -11.43, p = 0.000. It suggests that cooperative membership has an effect on resource access, as indicated by the change in their estimated monthly consumption expenditures. The study also found that cooperative membership enhances the teachers’ resource access and turns their capabilities into functionings through the provision of meals, financial benefits, and collegial and moral support. The cooperative officials’ slow decision-making, competition from donor and school-managed canteens, and prohibition of sales outside the designated class breaks are the problems being faced by the teachers.